Efisiensi Sistem Irigasi Pipa untuk Mengidentifikasi Tingkat Kelayakan Pemberian Air dalam Pengelolaan Air Irigasi - Afri Fajar; Muhammad Yanuar J. Purwanto; Suria Darma Tarigan (Balai Teknik Irigasi, 2016)
Irrigation water loss that commonly occurs in an agricultural area are runoff and deep percolation. Pipe irrigation has reached 98% efficiency because it can control the use of water as needed and has no seepage for water supply. Distance of paddy field’s inlet should also be a considered factor aside from irrigation technology. Rice field’s inlet distance affect the water distribution in a fields plot as they relate to application efficiency (Ea) and the efficiency of water distribution (Ed). The method used in this research was descriptive method that collect primary data and secondary data. The experiment plots were installed with irrigation pipes. The results showed Ed values above 90% in conventional and System of Rice Intensification (SRI). This explains the distribution of water in pipe irrigation evenly throughout the planting area. Ea value on experimental plots ranged between 76% - 98%. This is because of the occurrence of deep percolation and surface flow at the conventional fields, which causes decrease in efficiency. The paddy field inlets distance simulation results showed that good Ea (≥ 90%) obtained at a distance of 30 m with SRI water application gave water saving up to 10,25%. The feasibility of the water application on the value of Ea was obtained from the level of application of irrigation water’s pattern to conventional paddy at vegetative phase is critical at a distance of 170 m, while the generative phase is critical at a distance of 75 m and very critical at 178 m. SRI paddy field gives the value of feasibility of providing water at vegetative phase becomes near critical at a distance of 170 m, while the generative phase becomes critical at a distance of 150 m.